Поетична творчість Івана Гнатюка за радянських часів (19601970-ті рр.) - Колошук, Надія Георгіївна (Східноєвропейський національний університет імені Лесі Українки, 2013)
1. У статті йдеться про видиме та приховане у проблематиці, в образі ліричного героя лірики, автор якої прийшов у літературу в 1960-х рр., але через складні обставини долі, зумовлені трагічною історією України, зміг уповні реалізувати свій талант значно пізніше. Чимало відповідних радянській легальній літературі тем та мотивів мають у його опублікованій своєчасно і залишеній у сховку до кращих часів творчості неповторне індивідуальне вираження. The article deals with some visible and latent problems in the lyric character of the poetry. The author of the lyrics appeared in literature in the 1960s. But he managed to realize his talent later because of difficult circumstances caused by the tragic history of Ukraine. Quite a few themes and motifs of his works are correspondent to the Soviet legal literature and have unique individual expression. But they were published in proper time and hid till better times. The task of the research is to read the collections of works of the 1960s – 1970s (the period of consolidation of the poet’s professional mastery and at the same time his survival under the eyes of KGB and under the pressure of censorship) underscoring the possible preteritions which are nowadays evident when comparing with his partially restored earlier / camp lyrics. The form of the majority of Gnatiuk’s poems are classic. The author’s mastery became a guarantee of the artist’s inner firmness and independence.
Keywords: лірика Івана Гнатюка; старші шістдесятники; поетична традиція; провідні мотиви; віршова поетика; ліричний герой